Pengaruh Current Ratio (CR), Return On Equity (ROE), Net Profit Margin (NPM) dan Earning Per Share (EPS) Terhadap Harga Saham PT Bank Negara Indonesia Periode 2011-2022 - Yamin, Mohammad Yamin; Fitriani, Melisa Eliya (Management Research and Business Journal, 2024)
This research aims to determine and analyze (1) the effect of Current Ratio (CR) on Stock Prices, (2) the effect of Return On Equity (ROE) on Stock Prices, (3) the effect of Net Profit Margin (NPM) on Stock Prices, (4) ) the influence of Earning Per Share (EPS) on Share Prices, (5) the influence of Current Ratio (CR), Return On Equity (ROE), Net Profit Margin (NPM) and Earning Per Share (EPS) on Share Prices. The data used in this research was obtained from the Published Financial Report of PT Bank Negara Indonesia Tbk for the 2011-2022 period. The method used in this research is multiple linear regression involving classical assumption tests, followed by partial significance using hypothesis testing, namely the t test, while to find out jointly, the f test uses a significance level of 5%. The research results show that partially the EPS variable has a significant effect on stock prices. Meanwhile, the CR, ROE and NPM variables do not have a significant effect on share prices. Simultaneously, the CR, ROE, NPM and EPS variables influence stock prices. The adjusted R-squared value in this study is 0.759, which means that the ability of the independent variable to explain variations in the dependent variable is 75.9% while the remaining 24.1% is explained by other independent variables outside the model.